Age at first calving and dairy productivity of Holstein cattle in the central coast of PeruX - Sessarego D., Emmanuel (2020)
The aim of this study was to determine the effect of age at first calving (AFC) on the standardized production of milk (SMP) of the first and second lactation and interval between the first two calvings (CI) in Holstein cows of the Lima region, Peru. Records of 4215 cows from nine farms, registered in the Dairy Productivity Service of the National Agrarian University La Molina, between January 2003 and December 2012 were analysed. The information was analysed through descriptive statistics and by a mixed linear model, using SAS 9.4. The average AFC was 24.9 ± 2.3 months. The AEPP influenced on the SMP (p=0.0008), but not in the IEP (p=0.3969). Likewise, significant differences were found (p<0.01) between the two lactations, between the four seasons of the year and between the 10 years evaluated for the two variables under study. In conclusion, higher SMP and lower CI were observed at intermediate ages (22-30 months), so the optimal AFC would be around 22 months to achieve maximum productive performance.